Predictive Value of C-Reactive Protein for Early Postoperative Complications in Children After Hypospadias Surgery - Ji, Fengming; Tang, Haoyu; Wu, Chengchuang; Chen, Li; Wang, Huake; Yan, Bing (Frontiers in Pediatrics, 2021)
Background: To explore the predictive value of postoperative C-reactive protein in patients with hypospadias for postoperative complications and the risk factors. Methods: The clinical and follow-up data of 106 patients who were treated with operations at Kunming Children’s Hospital in 2020 were respectively analyzed. According to the occurrence of postoperative complications, the patients were divided into two groups. 25 patients with postoperative complications were complications group, and 81 without postoperative complications were the control group. The baseline data, clinical characteristics, laboratory test indexes, and outcome of the two groups were collected. Receiver operating characteristic (ROC) was used to calculate the optimal cut-value of C-reaction protein (CRP). Logistic regression was used to analyze the risk factors of hypospadias after surgery. Probability value （P-value）of ＜ 0.05 was considered statistically significant. Results: According to the result of ROC curve, the optimal cut-value of CRP was 11.7 mg/L. Logistic regression showed the length of urethral defect, the urethral material, the operative produce, and the postoperative CRP level were related to the occurrence of postoperative complications of patients with DCC. The length of urethral defect and the CRP level were the independent risk factors of the prognosis of hypospadias patients. The CRP level was related to the occurrence of postoperative complication and fistula. Conclusions: Postoperative CRP level can be used as a reliable marker for predicting the prognosis of hypospadias patients.